Differences in the element contents between gunshot entry wounds with full-jacketed bullet and lead bullet - Wunnapuk K. (2014)
To elucidate characteristics of gunshot residues in gunshot entry wounds with full-jacketed and lead bullets, element contents in entry gunshot wounds and control skins were analyzed by inductively coupled plasma-atomic emission spectrometry (ICP-AES). It was found that a high content of Fe and Zn was deposited in the gunshot entry wounds with full-jacketed bullet, whereas a high content of Pb was deposited in the gunshot entry wounds with lead (unjacked) bullet. It should be noted that the content of Pb was significantly higher in the gunshot entry wounds with lead bullet than in those with full-jacketed bullet. Regarding the relationships among elements, it was found that there were significant direct correlations between Pb and either Sb or Ba contents in both gunshot entry wounds with full-jacketed and lead bullets. As Pb increased in both gunshot entry wounds, Sb and Ba also increased in the wounds. © Humana Press Inc. 2007.